Meta-analysis reveals benefits of co-inoculation of soybean with Azospirillum brasilense and Bradyrhizobium spp. in Brazil - Barbosa, Julierme Zimmer; Hungria, Mariangela; Sena, João Victor da Silva; Poggere, Giovana; dos Reis, André Rodrigues [UNESP]; Corrêa, Rodrigo Studart (Elsevier, 2021)
Co-inoculation of soybean with Azospirillum brasilense and Bradyrhizobium spp. is an increasing practice in Brazil, but little is known about the conditions that maximize crop efficiency. In this study, data from field experiments run between 2009 and 2020 in Brazil were gathered to evaluate which environmental and agronomic conditions affect the response of soybean to bacterial co-inoculation. Results showed that co-inoculation of soybean increased root mass in 11%, nodule number in 5.4%, nodule mass in 10.6%, N concentration in shoots in 2.8%, grain yield and N concentration in grains in 3.2% and 3.6% respectively compared to the conventional single inoculation with Bradyrhizobium spp. Grain yield was used to discriminate co-inoculation efficiency, and soybean was more responsive to the simultaneous inoculation with B. japonicum and B. diazoefficiens in sandy soils, non-tillage system, tropical climate, soybean cultivars with determinate growth habit, and grain yield class lower than 3500 kg ha−1. Co-inoculation can also be important to mitigate the effects of water stress on plants. Co-inoculation of soybean with A. brasilense and Bradyrhizobium spp. demonstrated to be an efficient technology that contributes to the sustainability of soybean production.
Keywords: Bacterial soil inoculation; Grain yield; Soybean nodulation; Sustainable biotechnology; Water deficit